Evaluation and Comparison of Complete Dentures’ Complaints: Post-insertion - Ahmad, areej (Iraqi National Journal of Nursing Specialties, 2010)
Aims: This study aims to compare patients’ complaints and problems of wearing complete dentures. Methodology: The sample included 40 Iraqi patients who are wearing complete dentures from about five years ago. They were selected randomly with a age range between (55–65) years. The questions asked to the patients were listed according to the recent classification of post-insertion problems. Result: The results showed that the percentage of patient’s complaint from adaptation problems (62.1%) was higher than looseness problems (61.3%) and discomfort problems (39.3%) as followed. Recommendation: Dentists need thorough knowledge of anatomy, physiology, pathology and psychology. The assessing of the psyche and emotions of patients is extremely complex long period study at the same patient will give the more about this subject.